Attitudes towards Substance Use Disorders among Students in the Social Sciences: The Role of Gender and Terminology. (3rd February 2020) - Feingold, Daniel
Abstract: Background: Negative attitudes towards individuals with substance use disorders (SUDs) have been consistently reported within the general population, as well as among health professionals and medical students. Objectives: To explore attitudes towards SUDs held by students in the social sciences, the future-to-be mental health professionals, as well as factors, which may affect these attitudes. Methods: Undergraduate and graduate students in the social sciences (psychology, social work, criminology; N  = 184), were presented a vignette describing an individual with substance-related problems. Participants were randomly assigned with one of two vignettes, either addressing him as "suffering from substance use disorder" or as an "addict." Attitudes were assessed by exploring the degree to which participants perceive the described individual as posing social threat and in need of treatment. Results: Women generally perceived individuals with SUDs as in more need for treatment compared to men. Men, but not women, were significantly affected by the terminology used, with less negative attitudes reported when using medical terminology. Conclusion: Gender differences in attitudes towards individuals with SUDs may be present in earlier stages of mental health professionals' career. More emphasis should be given on the use of non-stigmatizing terminology among students in the social sciences, particularly men.